Essentialist thinking predicts culpability and punishment judgments. Issue 3 (16th March 2022) - Xu, Yian; Berryessa, Colleen M.; Dowd, Mackenzie; Penta, Darrell; Coley, John D.
ABSTRACT: People often perceive social groups (e.g. ethnic groups, occupations, gender groups) as having fixed membership and discrete boundaries. This paper proposes that essentialist beliefs about abstract crime concepts, as naturally defined and universally coherent, play a role in culpability and sentencing judgments. In three studies, a general sample of college students (Study 1, n  = 52), a lay public sample recruited from MTurk (Study 2, n  = 102), and a sample of college students recruited from criminal justice classrooms (Study 3, n  = 62) read crime vignettes and made culpability and sentencing decisions. We measured essentialist beliefs about crime categories by using an adapted essentialism scale for crimes, hypothesizing that essentialist tendencies would predict higher culpability ratings and harsher punishments. Results showed that lay participants had an overall tendency to endorse essentialist statements, and their essentialist ratings significantly predicted culpability and sentencing judgments with regards to the corresponding crimes. In contrast, students with formal education in criminal justice showed significantly weaker essentialist thinking about crime concepts, and their essentialist ratings did not predict culpability and sentencing outcomes. The current findings provide new evidence regarding how essentialist thinking and subject matter knowledge frames lay understandings about crime concepts, and how such intuitive beliefs may systematically influence legal judgments.